Mini Review : Liver Fibrosis Mechanism - Yuniarti, Wiwik Misaco; Primarizky, Hardany (KnE Life Sciences, 2017)
Liver fibrosis is the process of wound healing in the liver that caused by a various causes. The longer time of wound healing process, the more severe disorder will be. This chronic condition is characterized by excessive deposition of extracellular matrix then ended with fribrosis. This mini review describes about the phase of liver fibrogenesis. Even though there are many variations of fibrogenesis in animals and human, in general there are three fibrogenic cells that involved in fibrogenesis. These three cells are fibroblast or endogenous fibroblast like-cells, epithelial to mesenchymal transition (EMT), and fibrocytes that derived from bone-marrow. Keywords : liver, fibrosis, fibroblast, EMT, fibrocytes, collagen